2020
DOI: 10.1017/s1479262120000325
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in jackfruit (Artocarpus heterophyllus Lam.): insights into fruit characterization for the identification of superior genotypes

Abstract: Jackfruit (Artocarpus heterophyllus Lam.) is a nutritious crop from the Moraceae family. The current study was undertaken to evaluate the phenotypic diversity of fruit characteristics using a set of 27 standardized fruit descriptors to describe 28 jackfruit genotypes. These data were used to identify the superior jackfruit genotype that could be used for commercial cultivation. The data revealed a wide range of differences among the genotypes for all the traits studied. Cluster analysis classified the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Swami et al (2018) [17] observed that 18.60 to 60 percent pulp obtained from jackfruit and Garje (2023) [13] reported that the pulp recovery from jackfruit was 39.46 percent. According to Dhakar (2020) [14] , each fruit's core weight ranged from 0.20 to 1.16 kg. According to Maiti et al (2002) [15] , Cluster-11 jackfruit had the greatest rind weight (3.359 kg), followed by Cluster -10 (2.611 kg).…”
Section: Resultsmentioning
confidence: 99%
“…Swami et al (2018) [17] observed that 18.60 to 60 percent pulp obtained from jackfruit and Garje (2023) [13] reported that the pulp recovery from jackfruit was 39.46 percent. According to Dhakar (2020) [14] , each fruit's core weight ranged from 0.20 to 1.16 kg. According to Maiti et al (2002) [15] , Cluster-11 jackfruit had the greatest rind weight (3.359 kg), followed by Cluster -10 (2.611 kg).…”
Section: Resultsmentioning
confidence: 99%
“…In India, Indonesia, Nepal, Malaysia, Thailand, the Philippines, Sri Lanka, Vietnam, and Bangladesh, jackfruit collections for evaluation and selection are limited and therefore, the information available on the performance of the genotypes is also limited (IPGRI, 2000;Haq and Hughes, 2002). India and Bangladesh have reported a moderate level of jackfruit genetic diversity erosion (Dhakar et al, 2020). The most desirable varieties grown in India are low in productivity, storage, and processing quality.…”
Section: Introductionmentioning
confidence: 99%